Clinical Research in Neonates: Redesigning the Informed Consent Process in the Digital Era - De Sutter, Evelien; Coopmans, Birte; Vanendert, Femke; Dooms, Marc; Allegaert, Karel; Borry, Pascal; Huys, Isabelle (Frontiers in Pediatrics, 2021)
Background: Currently, many initiatives are devoted to optimizing informed consent for participation in clinical research. Due to the digital transformation in healthcare, a shift towards electronic informed consent (eIC) has been fostered. However, empirical evidence on how to implement eIC in clinical research involving neonates is lacking. Methods: Semi-structured interviews were conducted with 31 health care professionals active in Belgium or the Netherlands. All health care professionals had experience in conducting clinical research involving neonates. Interviews were audio-recorded, transcribed and analyzed using the framework method. Results: Interviewees generally supported the use of eIC in clinical research involving neonates. For example, eIC could enable parents to receive study feedback via the eIC system. Requirements were expressed for parental involvement to decide on which feedback would be appropriate to return. Moreover, experts specialized in presenting information and designing electronic systems should be involved. Broad consensus among health care professionals indicates that the face-to-face-interaction between parents and the research team is vital to establish a relationship of trust. Therefore, it is necessary that the use of eIC runs alongside personal interactions with the parents. Concerns were raised about the accessibility of eIC to parents. For this reason, it was suggested that parents should always be given the possibility to read and sign a paper-based informed consent form or to use eIC. Conclusions: Healthcare professionals’ views indicate that the use of eIC in clinical research with neonates may offer various opportunities. Further development and implementation will require a multi-stakeholder approach.